(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The pathological erasure of dental hard tissues is one of the urgent problems of modern dentistry, which is due to the high prevalence of this pathology and its significant impact on the quality of life of patients.